Sensory evaluation of lamb produced under different production systems from Uruguay and Europe - Sañudo C.; San Julián R.; Campo M.; Olleta J.L.; Font i Furnols M.; Oliver M.A.; Álvarez I.; Cañeque V.; Branscheid W.; Wicke M.; Nute G.R.; Montossi F. (Mediterranean livestock production: uncertainties and opportunities, 2008)
Some geographical areas in South America have a very high potential in ruminant meat production (i.e., Humid Pampas). This meat, produced at low cost under grazing conditions, has an undoubted growing potential and represents one of the main exports from those countries to USA and Europe. The aim of this study was to compare, with a trained taste panel, Uruguayan lamb aged for 20 days (11.1 and 19.4 kg carcass weight being 3-4 and 12-13 months old, respectively) with European lambs, aged for 7 or 20 days. European lambs were produced in Spain (10.2 kg carcass weight and 3 months of age), United Kingdom (22.8 kg from commercial animals) and Germany (23.2 kg and 4-6 months old). Results showed that lamb type had a significant effect in all the parameters considered, except in lamb flavour intensity, and that ageing had a strong influence in lamb sensory profile. The key factors related to the differences found in the sensory evaluation between lamb meats are highlighted.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)